Electrostatic interactions at the five-fold axis alter heparin-binding phenotype and drive enterovirus A71 virulence in mice - Shimizu, Hiroyuki; Tee, Han Kang; Tan, Chee Wah; Yogarajah, Thinesshwary; Lee, Michelle Hui Pheng; Chai, Hann Juang; Hanapi, Nur Aziah; Yusof, Siti R.; Ong, Kien Chai; Lee, Vannajan Sanghiran; Sam, I-Ching; Chan, Yoke Fun (Public Library of Science, 2019)
Enterovirus A71 (EV-A71) causes hand, foot and mouth disease epidemics with neurological complications and fatalities. However, the neuropathogenesis of EV-A71 remains poorly understood. In mice, adaptation and virulence determinants have been mapped to mutations at VP2-149, VP1-145 and VP1-244. We investigate how these amino acids alter heparin-binding phenotype and shapes EV-A71 virulence in one-day old mice. We constructed six viruses with varying residues at VP1-98, VP1-145 (which are both heparin-binding determinants) and VP2-149 (based on the wild type 149K/98E/145Q, termed KEQ) to generate KKQ, KKE, KEE, IEE and IEQ variants. We demonstrated that the weak heparin-binder IEE was highly lethal in mice. The initially strong heparin-binding IEQ variant acquired an additional mutation VP1-K244E, which confers weak heparin-binding phenotype resulting in elevated viremia and increased virus antigens in mice brain, with subsequent high virulence. IEE and IEQ-244E variants inoculated into mice disseminated efficiently and displayed high viremia. Increasing polymerase fidelity and impairing recombination of IEQ attenuated the virulence, suggesting the importance of population diversity in EV-A71 pathogenesis in vivo. Combining in silico docking and deep sequencing approaches, we inferred that virus population diversity is shaped by electrostatic interactions at the five-fold axis of the virus surface. Electrostatic surface charges facilitate virus adaptation by generating poor heparin-binding variants for better in vivo dissemination in mice, likely due to reduced adsorption to heparinrich peripheral tissues, which ultimately results in increased neurovirulence. The dynamic switching between heparin-binding and weak heparin-binding phenotype in vivo explained the neurovirulence of EV-A71. © 2019 Public Library of Science. All rights reserved.